A chemoselective cleavable fluorescence turn-ON linker for proteomic studies. Issue 100 (30th November 2017) - Liew, Si Si; Du, Shubo; Ge, Jingyan; Pan, Sijun; Jang, Se-Young; Lee, Jun-Seok; Yao, Shao Q.
Abstract : We have developed a trifunctional cleavable fluorescence turn-ON linker for chemoproteomic applications. Abstract : We have developed a trifunctional cleavable fluorescence turn-ON linker for chemoproteomic applications. This novel linker, which became highly fluorescent only upon cleavage of the azo bond, was successfully used for in situ proteome profiling/target identification and studies on newly synthesised proteomes.